Kronik tromboembolik pulmoner hipertansiyon tedavisinde pulmoner tromboendarterektominin yeri: Olgu sunumu - (:unkn) unknown (My University, 2013)
Pulmoner tromboendarterektomi (PEA), seçilmiş kronik tromboembolik pulmoner hipertansiyon (KTEPH) hastalarının tek tedavi seçeneğidir. Pulmoner trom- boendarterektomi, artmış pulmoner vasküler direnç (PVR) ve pulmoner arterlerde proksimal segment hastalığı olan hastalarda hayat kurtarıcı olabilir. Yetmiş iki yaşında erkek olguda, kronik tromboemboliye bağlı pulmoner arter dallarında %50-80 oranında tıkanma var idi. Ekokardiyografide pulmoner arter basıncı (PAB) 110 mmHg, sağ kalp kateterizasyonunda ortalama PAB 43 mmHg ve PVR 850 dyn/s/cm-5 idi. Kronik tromboembolik pulmoner hipertansiyon tanısı konulan hastaya PEA yapıldı. Pulmoner arter basıncı ameliyat sonrası 15. günde 40 mmHg’ya indi. Hasta 22. günde ani gelişen kardiyak arrest nedeni ile kaybedildi. Kronik trombo- embolik pulmoner hipertansiyon olgularında en etkili tedavi yaklaşımı cerrahidir. Ameliyat sonrası mortalite- yi azaltmak için tüm risk faktörleri dikkatlice değerlen- dirilmelidir. Bu makalede, başarılı geçen PEA ameliyatı sonrası kaybedilen bir KTEPH olgusu sunuldu.

Pulmonary thromboendarterectomy (PEA) is a single treatment of choice in selected patients with chronic thromboembolic pulmonary hypertension (CTEPH). Pulmonary thromboendarterectomy may be life- saving for patients with increased pulmonary vascular resistance (PVR) and proximal segment disease of the pulmonary arteries. A 72-year-old male case had a 50-80% occlusion in pulmonary artery branches due to chronic thromboembolism. Echocardiography revealed a pulmonary artery pressure (PAP) of 110 mmHg, while right heart catheterization showed a mean PAP of 43 mmHg and PVR of 850 dyn/s/cm-5. The patient who was diagnosed with CTPEH underwent PEA. Pulmonary artery pressure was reduced to 40 mmHg at postoperative day 15. The patient died on postoperative day 22 due to a sudden cardiac arrest. Surgery is the most effective treatment approach for CTPEH cases. All risk factors should be carefully evaluated to reduce postoperative mortality. In this article, we present a case of CTEPH patient who underwent a successful PEA and died following surgery.
The role of pulmonary thromboendarterectomy in management of chronic thromboembolic pulmonary hypertension: a case report
Keywords: Kalp ve Kalp Damar Sistemi